Analysis of Water Quality as an Indicator of Tourism Feasibility in the Waters of Batu Angus, Bitung City - Tampa, Ahazia Imanuel; Missa, Yudishinta; Hidayati, Desy Amalia; Boikh, Lebrina Ivantry; Palinggi, Rifka Liling; Harmos, Nikanor Hersal; Sejati, Martina Ayu (Sam Ratulangi University, 2025)
Coastal area have great potential for the development of marine tourism; however, their viability highly depends on environmental quality, particularly water quality. This study aims to analyze the physical and chemical parameters of water quality as indicators of tourism feasibility in the Batu Angus coastal area, Bitung City, North Sulawesi. Data collection was conducted at three representative sampling points using a descriptive quantitative approach, with parameters including temperature, water clarity, pH, salinity, dissolved oxygen (DO), ammonia, and visual observations of waste presence, oil films, and odors. The measurement results show that all parameters are within the seawater quality standards for tourism based on Government Regulation No. 22 of 2021. Temperature ranged from 29.05–29.17 °C, clarity reached up to 9 m, pH ranged from 7.85–8.11, salinity from 32.93–33.28 ppt, DO from 8.47–9.16 mg/L, and ammonia levels were very low (<LOD–0.005 mg/L). No signs of visual pollution, such as waste, oil layers, or odor, were detected. Based on these findings, the Batu Angus coastal waters are deemed suitable for development as a marine tourism destination. This study recommends sustainable management through regular water quality monitoring and an ecotourism approach to maintain marine environmental quality. Keywords: water quality, marine tourism, Batu Angus, physical-chemical parameters, tourism feasibility, ecotourism. Abstrak Perairan pesisir memiliki potensi besar dalam pengembangan pariwisata bahari, namun kelayakannya sangat bergantung pada kualitas lingkungan, khususnya kualitas air laut. Penelitian ini bertujuan untuk menganalisis parameter fisik dan kimia kualitas air sebagai indikator kelayakan wisata di kawasan perairan Batu Angus, Kota Bitung, Sulawesi Utara. Pengumpulan data dilakukan pada tiga titik representatif menggunakan pendekatan deskriptif kuantitatif dengan parameter yang meliputi suhu, kecerahan, pH, salinitas, oksigen terlarut (DO), amonia, serta pengamatan visual terhadap keberadaan sampah, lapisan minyak, dan bau. Hasil pengukuran menunjukkan bahwa seluruh parameter berada dalam kisaran baku mutu air laut kategori wisata berdasarkan PP No. 22 Tahun 2021. Suhu berkisar antara 29,05–29,17 °C, kecerahan mencapai 9 m, pH berkisar antara 7,85-8,11, salinitas berkisar antara 32,93-33,28 ppt, DO berkisar antara 8,47–9,16 mg/L, dan kadar amonia sangat rendah (<LOD–0,005 mg/L). Tidak ditemukan indikasi pencemaran visual seperti sampah, lapisan minyak serta bau. Berdasarkan hasil tersebut, perairan Batu Angus dinyatakan layak untuk dikembangkan sebagai kawasan wisata bahari. Penelitian ini merekomendasikan pengelolaan berkelanjutan melalui pemantauan kualitas air secara berkala dan pendekatan ekowisata untuk menjaga kualitas lingkungan laut. Kata kunci: kualitas air, wisata bahari, Batu Angus, parameter fisik-kimia, kelayakan wisata, ekowisata